Local Health Department Revenue Diversification and Revenue Volatility: Can One Be Used to Manage the Other?. Issue 1 (23rd January 2022) - Viall, Abigail H.; Bekemeier, Betty; Yeager, Valerie A.; Carton, Thomas
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: Revenue volatility—particularly in the form of sudden and significant reductions in funding—has been shown to negatively affect local health departments (LHDs) by impacting the amount and type of services delivered. This study examined the potential effectiveness of revenue diversification as a means of managing LHD financial risk. More specifically, we examine the relationship between revenue diversification and revenue volatility among LHDs in Washington State. Design and Setting: We applied fixed-effects linear regression models with robust standard errors to revenue data reported during 1998-2014 by all LHDs operating in Washington State. We also assessed the robusticity of our results to alternative specifications for revenue diversification and volatility. Main Outcome Measures: LHD revenue and revenue volatility. Results: Between 1998 and 2014, LHDs in Washington State were exposed to considerable upside and downside fiscal risks. While average revenue volatility was close to 0 (0.2%), observed values ranged from −35% to 63%. LHD revenues were already highly diversified: as measured using a reversed Herfindahl-Hirschman Index, diversification values ranged between 0.56 and 1.00. There is little evidence to suggest the existence of a statistically significant relationship between revenue diversification and volatility. Conclusions: Revenue volatility presents LHDs with important short- and long-term operational challenges. Our models suggest that revenue diversification did not reduce revenue volatility among Washington State LHDs in 1998-2014. Further research will need to examine whether revenue diversification reduces LHD financial risk in other settings.